2017
DOI: 10.12968/bjcn.2017.22.8.391
|View full text |Cite
|
Sign up to set email alerts
|

Real world challenges in delivering person-centred care: A community-based case study

Abstract: Community nurses face many challenges when trying to practice evidence based, person-centred care. Ongoing concerns regarding the impact of the 2013 Francis Report (Ford and Lintern 2017) suggest that individualised and holistic care is an impossible dream; one made harder when the client appears uncooperative. This paper presents a case study which sets out how some of these challenges were met in a potentially difficult situation experienced by a student nurse and her mentor in practice, in which the student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Despite the importance of managing the interpersonal process, however, it is often ignored in the evaluation of health care. Perhaps part of the reason it is ignored is that it is quite challenging to implement PCC in clinical practice (Riding et al, 2017). One way of moving towards the goal of PCC may thus be to start by increasing the focus and understanding of the concept of the patient pathway, since the way we understand the world and act in the world are based on our concepts (Lakoff & Johnson, 1980).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the importance of managing the interpersonal process, however, it is often ignored in the evaluation of health care. Perhaps part of the reason it is ignored is that it is quite challenging to implement PCC in clinical practice (Riding et al, 2017). One way of moving towards the goal of PCC may thus be to start by increasing the focus and understanding of the concept of the patient pathway, since the way we understand the world and act in the world are based on our concepts (Lakoff & Johnson, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Stange (2009) highlighted this issue when he quoted Osler, writing "it is more important to know what sort of person has a disease than to know what sort of disease a person has" (p. 102). It is therefore clear that the ideology of providing PCC is old, but the challenge of embedding it in everyday clinical practice still persists (Naldemirci et al, 2017;Riding, Glendening, & Heaslip, 2017). For example, a study found that doctors who were courteous often still systematically avoided dealing with the personal topics that patients brought up, even when they could be relevant to diagnosis and treatment (Agledahl, Gulbrandsen, Førde, & Wifstad, 2011).…”
Section: Pcc and Criticism Of Health Care Practicesmentioning
confidence: 99%
“…They were especially important in initially engaging clients as it was recognised that many of the groups PHNs work with often do not access services and are variously described as “hard to reach” or “seldom heard” (Cotton, 2015; Noonan, Galvin, Doody, & Jomeen, 2017). Once engagement has been achieved, encouraging sustained contact and motivating clients to make lifestyle changes were also viewed as a relationship‐building skill needed by the public health nurse (Astbury, Shepherd, & Cheyne, 2017; Olsen et al, 2017; Riding, Glendening, & Heaslip, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Whether this related to clients’ satisfaction with the service or what public health nurses perceived to be important in the delivery of any model or framework, the way public health nurses interacted with clients was seen to be fundamental to their success. This orientation or approach to practice involves being person‐centred, culturally sensitive, using good communication skills and building therapeutic relationships (Feather, Carter, Valaitis, & Kirkpatrick, 2017; Laholt, Guillemin, McLeod, Olsen, & Lorem, 2017; Noonan et al, 2017; Riding et al, 2017; SmithBattle, Lorenz, & Leander, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…By recognizing that each person is different with preferences and personality, putting these factors in the heart of nursing care is essential (Borbasi, Galvin, Adams, Todres, & Farrelly, 2013;Hemingway, Scammell, & Heaslip, 2012;Todres, Galvin, & Holloway, 2009). However it should be understood also that competing priorities can in many ways intervene and prevent quality and fully humanized care (Riding, Glendening, & Heaslip, 2017).…”
Section: People Centered Care Challenges In Nigeriamentioning
confidence: 99%